2008
DOI: 10.1007/s00431-008-0879-7
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces boulardii in childhood

Abstract: The mechanisms of action of S. boulardii depend mainly on the inhibition of some bacterial toxins, anti-inflammatory effects, and on stimulating effects on the intestinal mucosa such as trophic effects on the brush border enzymes and immunostimulatory effects. At present, in pediatric populations, there is evidence that S. boulardii is beneficial for the treatment of acute gastroenteritis and the prevention of antibiotic-associated diarrhea. More data are needed in other indications such as traveller's diarrhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 81 publications
0
16
0
1
Order By: Relevance
“…Several published data focus on hospitalized patients. However, for some probiotics, such as S. boulardii , the vast majority of data are obtained in ambulatory care and in the developing world [ 10 ]. As a result of strain and product specificities (especially for products containing mixtures of probiotic strains) and to be in agreement with the recommendations of official and scientific organizations, it is recommended to perform randomized controlled trials with each commercialized product [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several published data focus on hospitalized patients. However, for some probiotics, such as S. boulardii , the vast majority of data are obtained in ambulatory care and in the developing world [ 10 ]. As a result of strain and product specificities (especially for products containing mixtures of probiotic strains) and to be in agreement with the recommendations of official and scientific organizations, it is recommended to perform randomized controlled trials with each commercialized product [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that the mechanisms of action of S. boulardii in the treatment of diarrhea could include the following 4 aspects: i) effects of anti-bacterial toxins; ii) direct or indirect inhibition of growth of intestinal pathogens, such as Candida albicans , Salmonella , Yersinia ; iii) increase of short chain fatty acids concentrations; iv) immunomodulatory effects such as an increase in sIgA [ 13 ]. H. pylori interacts with the host immune response by upregulation of various cytokines, such as tumor necrosis factor-α, interferon-γ, interleukin (IL)-1, IL-6 and IL-8 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that S. boulardii had improved the post-treatment dyspepsia symptoms of H. pyloris infection without having a significant effect on the rate of H. pylori eradication (Cindoruk et al, 2007). Recently, Vandenplas et al (2009) suggested that S. boulardii alters the structure of H. pylori . Further studies are required for better understanding of yeast probiotics mechanisms.…”
Section: Applications Of Antagonistic Activities Of Yeastsmentioning
confidence: 99%